2016
DOI: 10.1080/02713683.2016.1183030
|View full text |Cite
|
Sign up to set email alerts
|

AMA0428, A Potent Rock Inhibitor, Attenuates Early and Late Experimental Diabetic Retinopathy

Abstract: Targeting ROCK with AMA0428 effectively attenuated outcome in an early DR model (STZ) and a late vasoproliferative retinopathy model (OIR). These findings make AMA0428 a promising candidate with an additional anti-inflammatory and neuroprotective benefit for DR patients, as compared with anti-VEGF treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 88 publications
3
14
0
Order By: Relevance
“…In addition, further cell-type specific analysis of diabetesinduced retinal neurodegeneration within the inner retina showed a significant reduction in RGC density starting in the early diabetic phase, further diminishing over time, all in line with earlier findings described in the mouse STZ 21,72,73 and the Ins2 Akita model. 74 Notably, some contradictory results have been reported in literature, in which neurodegeneration was found to be most prominent in the STZ-induced diabetic mice at later time points (e.g., 10-14 weeks) after diabetes onset, 30 or RGC death was not detected up to 6 months after diabetes induction.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, further cell-type specific analysis of diabetesinduced retinal neurodegeneration within the inner retina showed a significant reduction in RGC density starting in the early diabetic phase, further diminishing over time, all in line with earlier findings described in the mouse STZ 21,72,73 and the Ins2 Akita model. 74 Notably, some contradictory results have been reported in literature, in which neurodegeneration was found to be most prominent in the STZ-induced diabetic mice at later time points (e.g., 10-14 weeks) after diabetes onset, 30 or RGC death was not detected up to 6 months after diabetes induction.…”
Section: Discussionsupporting
confidence: 89%
“…The results of the present study are consistent with a previous report that involved intravitreal injection and reduced inflammation in the retina, and that showed another ROCK inhibitor, AMA0428, significantly reduced retinal leukocyte adhesion in the streptozotocin-induced murine diabetic model. 44 However, the present study administered the ROCK inhibitor systemically and did not investigate the topical administration of ripasudil, which is one of the limitations that should be further investigated in future studies. Because it has been previously reported that radiolabelled ripasudil reached the retina and choroid following the administration of eye drops in rabbits, 15,24 there are enough possibilities that topical administration of ripasudil could attenuate ocular inflammation both in the anterior and posterior segments of the eye.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the expression of Rho-kinase can be selectively blocked by its competitive inhibitors. Treatment with ROCK inhibitors improved type 2 diabetes in animal models [24]. The up-regulated Rho-kinase pathway was also reported in diabetic db/db mice, and the ROCK inhibitor was suggested to improve the diabetic complications [25].…”
Section: Discussionmentioning
confidence: 99%